A trial of the effective lifelong learning inventory (ELLI) : a case study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education (EdD) at Massey University, Manawatū - Hyett, Maureen Margaret (Massey University, 2018)
The purpose of education is to prepare learners for the world they are going to live in. Education should actively support learners to develop the capabilities they need to engage productively with the difficult and challenging problems that are part of today’s world. The Effective Lifelong Learning Inventory (ELLI) is a programme designed to assist in the development and measurement of the learning dispositions of: strategic awareness, changing and learning, meaning making, creativity, critical curiosity, learning relationships and resilience. This thesis has taken a case study approach to explore the process of the trial of ELLI within one urban secondary school. The introduction of the tool actively supported the developing learning culture of the students and the learning culture of the staff. Drawing on the perspectives of both staff and students and unpacking the difficulties associated with the implementation, this thesis analyses the process involved in trialling the tool. To document the trial process, data were collected from observations of all meetings and presentations, and interviews with both the teachers and students involved in the trial. The reasons the school undertook the trial were explored, through interviews with the principal and teachers, by examining the culture of learning and the professional learning history in the school. The GPILSEO model for sustainability of school change was used to examine the key factors of goals, pedagogy, institutions, leadership, spread, evidence and ownership of the trial process. The impact of the trial process on students was explored by examining their academic results, their ELLI profiles and listening to the students.
Keywords: Education (Secondary); Aims and objectives; New Zealand; Case studies; Curricula; School improvement programs; Curriculum enrichment; Learning, Psychology of